Ziswaf: zakat application to improve ease of recording zakat data in Indonesia - Komarudin, M.; Sophian, Ali; Septama, Hery Dian; Yulianti, Titin; Ikhsan, Muhamad; Zuhelmi, Tomy Pratama (WSEAS Press, 2023)
Maximizing zakat is one of the endeavors of the Indonesian government in alleviating poverty. However, the manual procedures used in the zakat management system are a hindrance because it takes too long to process data collection and distribute received zakat funds. The purpose of this research is to develop a zakat-recording application that is automatically and continuously synchronized across all user interfaces. Therefore, it can aid in ensuring that the worthiest or Mustahik are properly receiving zakat from the Muzakki (zakat payers) and that all transactions are legitimate. The research procedure used was the development of the Extreme Programming (XP) approach. The number of research subjects involved was 255 people, consisting of zakat ambassadors, group managers, area managers, local committees (called Panzisda), regional committees (called Panziswil), and institutional committees. With the assistance of the User Experience Questionnaire (UEQ), an evaluation of the newly developed system was performed. The findings of the evaluation of the system development demonstrate that users have provided satisfactory evaluations on several characteristics, including attractiveness (1.72), accuracy (1.75), efficiency (1.55), dependence (1.50), stimulation (1.72), and novelty (1.03). All of the data indicates positive evaluation results, which means that the developed application can be utilized to facilitate the process of zakat data recording and verification.